2004
DOI: 10.1007/s00216-003-2322-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of chemometric methods to the investigation of main microcontaminant sources of endocrine disruptors in coastal and harbour waters and sediments

Abstract: Identification, resolution and distribution of main microcontaminant sources of endocrine disruptors in Spanish harbours, coastal waters and sediments are investigated using chemometric methods. We investigated eighteen different endocrine disruptor chemical compounds, including non-ionic surfactants, their degradation products and linear alkylbenzene sulfonates, found in a total number of 74 samples (35 water samples and 39 sediment samples) over a period of 16 months from March 1999 to July 2000, and in 32 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…The study found that the geographic location of the EDC source could be reasonably identified using three principle components for water samples and four for sediment samples. Interestingly the study concluded that, although EDC "hot spots" could be generally identified using these techniques, the over all distribution of EDCs suggested ubiquitous sources (Peré-Trepat et al, 2004). This study demonstrates the potential for nonpoint sources of EDC and that control (through regulation) of point source discharges from wastewater treatment plants or industrial sources could be insufficient to reduce EDC to below active levels in water and sediment.…”
Section: Applications Of Bioassays and Biosensorsmentioning
confidence: 88%
See 2 more Smart Citations
“…The study found that the geographic location of the EDC source could be reasonably identified using three principle components for water samples and four for sediment samples. Interestingly the study concluded that, although EDC "hot spots" could be generally identified using these techniques, the over all distribution of EDCs suggested ubiquitous sources (Peré-Trepat et al, 2004). This study demonstrates the potential for nonpoint sources of EDC and that control (through regulation) of point source discharges from wastewater treatment plants or industrial sources could be insufficient to reduce EDC to below active levels in water and sediment.…”
Section: Applications Of Bioassays and Biosensorsmentioning
confidence: 88%
“…Moreover, the solubility values would suggest that most EDCs would generally not remain in solution. However, the EDCs in this Table have been identified in water samples collected throughout the world (Petrović et al, 2004;Peré-Trepat et al, 2004;Rice et al, 2003;Stachel et al, 2003;Ying et al, 2001;Ferguson et al, 2001;Thurman et al, 1992). In some cases EDCs have been found in groundwater and drinking water samples suggesting some type of soluble transport (Lopez-Roldan et al, 2004;Petrović et al 2003).…”
Section: Edc Fate and Transport With Bioassaysmentioning
confidence: 89%
See 1 more Smart Citation
“…Granulometric and geochemical normalization is used to overcome high affinity of metals for fine-grained sediments (Reid and Spencer 2009). Peré-Trepat et al (2004) have successfully applied log (x+1) transformation in water and sediment samples datasets of Spanish coast before PCA application to investigate and identify main sources of endocrine disruptor compound. Granulometric and geochemical normalizations have been applied by Reid and Spencer (2009) in Medway Estuary (South England) and Leardi et al (2001) in Venice lagoon as data pre-treatment methods before PCA application.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] to the resolution and quantification of mixtures in flow injection analysis [26], to the resolution of the different components in kinetic reactions and processes [27], to studies of conformational changes of polynucleotide [28], to protein folding processes [29], to determination of protein secondary structure [30], and to the resolution and apportionment of environmental sources of contamination [31].…”
Section: Introductionmentioning
confidence: 99%